Factors influencing the prevalence of trypanosomosis in Orma Boran (trypanotolerant) and Teso zebu (trypanosusceptible) cattle crosses in Teso District, western Kenya - Gachohi, John M.; Bett, Bernard K.; Murilla, G.A. (2009)
The objective of this study was to determine factors associated with occurrence of trypanosomosis in the first generation (F1) crossbreds between trypanotolerant Orma Boran and trypanosusceptible Teso zebu cattle in a trypanosomosis endemic area in Teso District, western Kenya. The offspring were screened for trypanosomosis and other haemoparasites using parasitological methods. Packed cell volume (PCV), body weights and tsetse density (FTD) were also determined. Factors considered in the analysis included sex, age, body weight and season of the year. Generalized linear mixed models (GLMM) were used for multivariable analysis to account for clustering of observations at the animal level and estimate outcome variance parameters.